Requirements for the repairing mortars of load-bearing walls of old buildings - Couto, J. Pedro (2007)
The importance and specificities of the mortar coverings have recently been object of discussion and analysis in the context of conservaton and rehabilitation of old buildings. Coverings and finishing are, many times, removed and replaced by inadequate solutions, whether from the constructional or architectonical point of view. The care and requirements of mortars in the rehabilitation of the masonry of old buildings go far beyond the need to replace or improve the structural security. The repair of mortars in old structures shoud also respect the cultural identity and the historical value of the buildings. Based on a literature review and a field research with parties and suppliers, this work presents the main requirements and guidelines regarding to mortars nterventions in load-bearing walls either in plasters with serious adherence and cohesion problems or consolidations. The basic principles for the selection of materials and intervention techniques that seek to adopt the better solutions for the rehabilitation of masonry coverings and structures of old buiIdngs were also established. Furthermore, it was notorious that mortars industry have been developed all the efforts with a view to responding to the constructive and functional requirements of these buildings.